Correlation of Polymorphism of IL-8 and MMP-7 with Occurrence and Lymph Node Metastasis of Early Stage Cervical Cancer - 吴素慧 卢实 陶慧娟 张莉 林维凤 尚海霞 解军 (Journal of Huazhong University of Science and Technology. Medical sciences, 2011)
The IL-8 and MMP-7 genes participate in the carcinogenesis of many malignancies,but the role of both genes in cervical cancer is not fully elucidated.The aim of this study was to determine the frequency of IL-8 and MMP-7 gene mutations and to assess their effects on the risk of early stage cervical cancer and lymph node metastasis.The clinical stage and histological grade of cervical cancer were also studied.The peripheral blood from the patients with early stage cervical cancers and normal controls was collected and the DNA was extracted.The incidence of IL-8 and MMP-7 gene mutations was assessed by using tetra-primer amplification refractory mutation system polymerase chain reaction（ARMS PCR） and restriction fragment length polymorphism（RFLP）.The data were statistically analyzed by x2 test.The results showed that：（1） The genotype frequency of IL-8-251AT and TT was significantly higher in the cervical cancer group than in the normal control group（OR=2.290 and 2.619 respectively,P=0.001）,and it was also higher in the lymphatic metastasis group than that without metastasis（OR=2.917,P=0.035）（2） The frequency of MMP-7-181G/G genotype was significantly higher in the cervical cancer group and in the lymphatic metastasis group（P〈0.05）（3） The incidence of IL-8 mutation was two times higher in Ⅱa cervical cancer group than in Ⅰb1 and Ⅰb2 cervical cancer group（P=0.006）.For the MMP-7 gene,there was statistically significant difference in the incidence of mutation between the Ⅰb1,Ⅰb2 and the Ⅱa（P=0.000）（4） Different histological types and different grades of cervical cancer had different incidence of mutations,statistically.It was suggested that there was significant difference in the genotype of IL-8-251TT and MMP-7-181GG polymorphism between the cervical cancer group and the lymph node metastasis group.Moreover,individuals with IL-8 T allele or MMP-7 G allele carriers were at significantly higher risk of cervical cancer,particularly the early（Ⅱa） and medium,poorly differentiated cervical cancer（G2＋G3）.